2015
DOI: 10.1080/01430750.2015.1100681
|View full text |Cite
|
Sign up to set email alerts
|

Heat transfer and fluid flow behaviour of a rectangular duct roughened with V-ribs with symmetrical gaps

Abstract: In the present work artificial roughness in the form V-ribs with symmetrical gaps have been applied on the heated surface to enhance the heat transfer in the limbs of V-ribs. Symmetrical gaps on both legs were provided by varying the relative gap width from 1 to 5 and number of gaps from 1 to 5. The relative roughness pitch, relative roughness height and aspect ratio of the rectangular duct are kept constant to the value of 10, 0.0433 and 12, respectively. The Nusselt number and friction factor of the artifici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…6.5. V-shape ribs [23][24][25][26][27][28][65][66][67][68][69]74 are of the shape of the English alphabet V, and its apex meets at the center of the duct. It has two inclined ribs meeting at halfway of the duct.…”
Section: Discussion and Future Scopementioning
confidence: 99%
See 1 more Smart Citation
“…6.5. V-shape ribs [23][24][25][26][27][28][65][66][67][68][69]74 are of the shape of the English alphabet V, and its apex meets at the center of the duct. It has two inclined ribs meeting at halfway of the duct.…”
Section: Discussion and Future Scopementioning
confidence: 99%
“…Maithani and Saini 27,69 carried out their investigation for V-ribs with symmetrical gaps roughness geometries. They have investigated the heat transfer and pressure drop of roughened SAH duct which is shown in supplementary Fig.…”
Section: Application Of Wire Ribs and Its Different Geometries In Sah...mentioning
confidence: 99%
“…They found maximum THP at P I /p = 0.6, r/e=3.5 and W/w = 7. Maithani et al [29] examined using V-shaped ribs with evenly spaced gaps as a type of artificial coarseness in a duct of a SAH. They reported that V-ribs with evenly spaced gaps artificial coarseness exhibited Superior performance compared other rib geometries.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some correlations have been presented for the Nusselt number and pressure drop in the proposed SAH with a AE 10% deviation. Maithani and Saini 43 presented a new design of SAH integrating V-ribs with symmetrical gaps. The maximum enhancement in terms of Nusselt number was obtained for a relative gap width of 4 and 3 gaps.…”
Section: Introductionmentioning
confidence: 99%